OCCURRENCE OF MATURE SPECIMENS OF METAPENAEUS BURKENROADI KUBO IN THE PULICAT LAKE - Muthu, M S; Manickam, P E Sampson (Indian Journal of Fisheries, 2011)
Mature females and males of Metapenaeus burkenroadi with fully developed ovaries and petasmae were collected from the Pulicat lake in January 1972. The possibility of their breeding inside the lake and the feasibility of utilizing this species for culturing in the Pulicati lake are indicated. Some morphological features of the specimens which are at variance with previous descriptions of the species are pointed out